Does trade integration imply growth in Latin America? Evidence from a dynamic spatial spillover model - F. Blasques; P. Gorgi; S. J. Koopman; J. Sampi (Tinbergen Institute, 2023)
To investigate the role of intra-regional trade integration on economic growth in Latin America, we develop a multilevel spatial production network model with time-varying parameters. The theoretical model is established for a multi-country and multi-sectoral economy. The reduced-form econometric framework relies partly on observation-driven dynamic processes. The finite-sample properties of the maximum likelihood estimates are investigated through a Monte Carlo study. The empirical study is for six countries in Latin America. The findings suggest that intra-country spillovers configure an important factor for explaining growth, while the importance of domestic spillovers is limited. The growth volatility is substantively reduced since 2005.
Keywords: C31; C32; F14; F43; 330; Spatial network model; multilevel model; time-varying parameters; economic modeling; trade liberization; growth.